Evaluation of Teachers' Literacy and Numeracy Skills: A Case Study on Certain Teachers' PPG Participants - Mutia Fonna; Ratna Unaida; Siraj Siraj; Halimatus Sakdiah; Ika Aulia Putri; Aura Firia Dewi (International Journal of Educational Research, 2024)
The Teacher Professional Education Program (PPG) aims to improve teachers' competence in carrying out the learning process, which in turn has an impact on improving the quality of education. The purpose of the research is to find out how to evaluate the literacy and numeracy skills of teachers participating in the PPG Certain Teachers. This study uses a qualitative approach, namely evaluation research with a case study method that focuses on one phenomenon. The design models used in CIPPO evaluation are context, input, process, product, and outcome. The population is all informants, namely PPG managers, PPG Coordinators, Lecturers, Pamong Teachers and PPG participants of Certain Teachers totaling 569 people. Data collection by document study, interview guidelines and observation guidelines. Qualitative data analysis uses the Miles and Huberman model, namely data reduction, data presentation and conclusion drawn. In general, based on the graduation percentage of 99.3% declared to have passed UKPPPG and 0.7% did not pass UKPPPG, it can be concluded that the literacy and numeracy skills of teachers participating in certain PPG Teachers are very good and the PPG program at LPTK Malikussaleh University can continue.